PENERAPAN TIGA PILAR CHARLOTTE MASON PADA PEMBENTUKAN KARAKTER SISWA KELAS II SDN JATIBARANG 03 - Inggar Rezha Listiary; Maria Agni Cahya Wulan; Mia Damayanti Damayanti; Ika Ratnaningrum Ratnaningrum (Jurnal Binagogik, 2025)
Charlotte Mason theory consists of three pillars : Atmosphere, Discipline, and Life. She emphasizes the importance of a joyful and enriching learning environment, the development of good habits from an early age, and the belief that all of life is a source of education. Her approach to learning moves beyond rote memorization, involving nature and high-quality books that instill strong character values. While Charlotte Mason's theory is widely known in homeschooling education, it remains less familiar in public and private schools. Therefore, this study was conducted at SDN Jatibarang 03 to examine the application of Charlotte Mason’s character values in a formal school setting. We employed a descriptive qualitative research method. The results show that SDN Jatibarang applies several aspects of Charlotte Mason’s educational principles, although there are some inconsistencies with her original theory.